Which physical tests are the most important for rugby league players? - Kain, M. (Journal of Australian Strength and Conditioning, 2016)
Testing is a vitally important aspect in any given sport as it helps both athletes and coaches assess athletic talent and identify physical abilities and areas in need of improvement. There is a large array of testing protocols to choose from for any given sport. This paper will detail the role of testing for the sport of rugby league and outline numerous testing options available to the coach. It will highlight both positives and negatives of the tests specific to the sport of Rugby League. Reference to current tests used at the elite level for Rugby League will be given and most importantly it will explain why each particular test is undertaken and what to do with the data once it is generated. This paper will also address the validity of testing, the best time to test athletes and length of time between tests.